Effect of drip irrigation regimes and nitrogen levels on growth, yield and economics of aerobic rice (Oryza sativa L.) - Goud, B Raghavendra; Reddy, G Prabhakara; Chandrika, V; Naidu, MVS; Sudhakar, P; Reddy, K Madhusudhana; Sagar, G Karuna (ORYZA-An International Journal of Rice, 2022)
Water supply to agriculture especially rice will be affected in the future because of climate change and increased demand of water for non-agricultural use. To sustain rice production, focus should be on water saving rice production systems such as aerobic rice, which may further reduce water requirement when combined with drip irrigation. Hence, a field experiment to study the influence of drip irrigation regimes and nitrogen levels on growth, yield and economics of aerobic rice was conducted at Tirupati, Andhra Pradesh, during the rabi seasons of 2019-20 and 2020-21. Four main plot treatments consisting of irrigation regimes based on pan evaporation i.e., drip irrigation at 1.25 Epan, 1.50 Epan, 1.75 Epan, 2.00 Epan and four sub plot treatments comprising of four doses of nitrogen i.e., 75 % RDN (90 kg N ha-1), 100 % RDN (120 kg N ha-1), 125 % RDN (150 kg N ha-1) and 150 % RDN (180 kg N ha-1) were tested in split plot design replicated thrice. Significantly higher plant height, number of tillers, yield attributes, grain yield, straw yield and gross returns were recorded with drip irrigation regime of 2.0 Epan over other irrigation regimes, but was comparable with drip irrigation at 1.75 Epan. While, higher net returns and B:C ratio were recorded with drip irrigation regime of 1.75 Epan which was at par with 2.0 Epan and 1.5 Epan. Aerobic rice grown with 180 kg N ha-1 proved to be superior with respect to plant height, number of tillers m-2, panicle weight, grain yield, straw yield, gross returns and net returns which was however comparable with 150 kg N ha-1 in case of panicle number, filled grains per panicle, test weight and B:C ratio. Among the interaction combinations, drip irrigation regime of 2.0 Epan along with 180 kg N ha-1 resulted in superior plant height, tillers m-2, yield attributes, grain yield, straw yield, gross returns, net returns and B:C ratio which was statistically at par with drip irrigation regime of 1.75 Epan along with 180 kg N ha-1 except in case of tiller number.